PENGARUH KOREAN WAVE DALAM STRATEGI PEMASARAN TOKOPEDIA DI INDONESIA PADA TAHUN 2019-2020 - Wardah ‘Aliyah; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes the influence of the Korean Wave on Tokopedia's marketing strategy in Indonesia in 2019-2020. The Korean Wave has become a global phenomenon that can't be separated from the role of non-state actors in the process of spreading it. BTS is one of the actors from the Korean Wave who is categorized as a global artist and brings a positive message to several young people. This Korean Wave phenomenon was then used by several companies, one of which was Tokopedia. In 2019, Tokopedia officially appointed BTS as the brand ambassador who will carry the brand image of Tokopedia. According to Tokopedia, BTS has a shared vision and can help convey Tokopedia's message to the world. This received good reception and support from several fans.This study uses a qualitative method, with data collection through literature studies sourced from several books, journals, articles, and websites. This study uses the perspective of Economic Liberalism and the theory of Economic Globalization. The results of this research indicate that the influence of the Korean Wave on the marketing strategy of Tokopedia has increased sales at Tokopedia. Based on the data obtained, Tokopedia experienced an increase in the frequency of order volume by 109.3%, an increase in transactions by 81.1%, and an increase in sales volume by 133% with the majority of sellers consisting of MSMEs. In addition, Tokopedia experienced an increase of 5 million visits and as many as 5,000 items were sold every minute at the ‘Waktu Indonesia Belanja’ event which was filled with BTS as brand ambassadors and several well-known idol groups from South Korea. The Indonesian government also supports Tokopedia to help MSMEs to be able to enter the international market.Keywords: Korean Wave, Marketing Strategy, Tokopedia